How hospital chaplains develop and use rituals to address medical staff distress - Robert Klitzman; Jay Al-Hashimi; Gabrielle Di Sapia Natarelli; Elizaveta Garbuzova; Stephanie Sinnappan (Elsevier, 2022)
Physicians and nurses face high levels of moral distress and burnout, exacerbated by the COVID-19, yet are often busy, without time for extended interventions. Hospital chaplains have recently been asked to assist staff, but many questions arise concerning whether they do so, and if so, how and when, and whether they may vary in doing so. Thirty-one telephone interviews of ∼1 ​h each were conducted with 21 board-certified chaplains to examine these and related issues. Respondents reported how they help staff, often creating, on their own, innovative kinds of practices that appear to take the form of rituals. These rituals vary in audience (physicians, nurses and/or other staff, with or without patients or families), form (from open-ended to structured), formality (from formal to informal), timing (at hospital discharge, time of death or after death), duration (from a few minutes to longer), frequency (from once to several times or ongoing), content (expressing and/or reframing feelings and experiences), and activities (e.g., talking, eating and/or making commemorative objects). Such rituals can help staff cope with death, grief, and other stresses. Challenges arise, including hospital leaders' wariness, resistance or lack of support, and staff time constraints, making briefer sessions more practical. These data highlight how chaplains can assist staff through use of rituals, and learn from innovations/initiatives devised by colleagues elsewhere. Chaplains can thus enhance what they do as individuals and as a profession. These data have critical implications for future research, education and practice for physicians, nurses, hospital administrators, chaplains and others.